Cardiotoxicity of trastuzumab emtansine (T-DM1): a single-center experience. Issue 12 (December 2021) - Acibuca, Aynur; Sezer, Ahmet; Yilmaz, Mustafa; Sumbul, Ahmet Taner; Demircan, Senol; Muderrisoglu, Ibrahim Haldun; Ozyilkan, Ozgur
Objective: New anti-cancer drugs promise to increased survival benefits and reduce adverse events. Trastuzumab emtansine (T-DM1) is a novel anti-human epidermal growth factor receptor 2 agent that has shown minimal cardiotoxicity in clinical trials. However, data on real-life outcomes are required. Methods: A retrospective review of our center's medical records was performed, including female patients aged ≥18 years with a diagnosis of metastatic breast cancer who were treated with T-DM1. Descriptive statistics were used to investigate clinical features that could increase the risk of cardiotoxicity. Cardiotoxicity was determined by comparing pre and post-T-DM1 echocardiogram results and was defined as a decrease in the left ventricular ejection fraction (LVEF) >10% to below 55%. Results: Data from 41 female patients with a mean age of 52 ± 11.5 years were evaluated. A significant LVEF decrease (from 59% to 33%) was observed in one patient during T-DM1 treatment. Further investigation showed that this decrease was due to underlying coronary artery disease, and LVEF recovered to the baseline value after coronary revascularization. Conclusion: T-DM1 seems to be safe in terms of cardiotoxicity. Real-life data with a larger sample size are still needed to confirm the cardiac safety of T-DM1.